Additive‐Enhanced Crystallization of Solution Process for Planar Perovskite Solar Cells with Efficiency Exceeding 19 %. Issue 72 (4th December 2017) - You, Shuai; Bi, Shiqing; Huang, Jing; Jia, Qiushuang; Yuan, Yuhe; Xia, Yanjie; Xiao, Zhenyu; Sun, Zhuzhu; Liu, Jiangfeng; Sun, Shujie; Zhao, Zhiqiang
Abstract: To reduce intrinsic defect density in perovskite films, various additives are often added into the precursor solution. In this paper, a novel solution, in which isopropanol (IPA) was added into the precursor solution, was developed for the preparation of normal planar perovskite solar cells (PSCs). A champion power conversion efficiency (PCE) of 19.70 % was achieved with this approach. By adding IPA into the precursor solution, CH3 NH3 PbI3 perovskite showed better crystallization and stability, indicating improved film quality. Because of the improved morphology of perovskite crystal, the PCE of PSCs increased. In addition, the unencapsulated PSCs retained high output for up to 40 days in air at room temperature, indicating the stability of PSCs. These results may provide a new avenue for manufacturing high efficiency and high stability PSCs. Abstract : Do you have IPA on tap? A novel solution approach, in which isopropanol (IPA) was added into the precursor solution was developed for the preparation of normal planar perovskite solar cells (PSCs). The resultant device, with very small hysteresis and high stability, had a higher power conversion efficiency (19.70 %) compared with the reference PSC without IPA additive (16.02 %).